Hsp90 Inhibitors and the Reduction of Anti-Cancer Drug Resistance by Non-Genetic and Genetic Mechanisms - Douglas M. Ruden; Xiangyi Lu; Luan Wang (MDPI AG, 2012)
In this review, we focus on how inhibitors of Hsp90 can help prevent the resistance to anti-cancer drugs by synergistically increasing their cancer killing abilities and thereby allowing them to function at much lower concentrations than normally used. Hsp90 helps to fold numerous client proteins, such as Akt, Raf, Src, chromatin-modifying proteins, nuclear hormone receptors, and kinetochore assembly proteins. We discuss four mechanisms by which Hsp90 inhibitors can potentially synergize with anti-cancer drugs: by making a drug-resistant protein that is a client for Hsp90 more sensitive to the drug, by increasing chromosomal aneuploidy and the effectiveness of DNA-damaging drugs, by inhibiting Trithorax proteins which trimethylate histone 3 at lysine 4 (H3K4me3) and thereby decreasing expression of tumor promoter genes, and by interacting with the negative elongation factor (NELF) complex in tumors. We also explain how the evolutionary capacitor function of Hsp90 can be exploited with inhibitors of Hsp90 by exposing new protein variants that can be targeted with other drugs, thereby opening new avenues of combination drug therapy to treat cancer. We believe that inhibition of these processes can increase the efficacy of Hsp90 inhibitors with other anti-cancer drugs.